PENGARUH LIMBAH TANDAN KOSONG KELAPA SAWIT DAN ABU BOILER TERHADAP BIBIT KELAPA SAWIT (Elaeis Guineensis Jacq.) - Malik, Amalia; Maghfiroh, Canggih Nailil; Halimah, Nur; Rizky, Dian; Puspita, Helda Jaya (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Oil palm is one of the plantation commodities with high economic value. Post-harvest processing at an industrial scale generates substantial waste, which requires proper management to prevent environmental pollution. Oil palm waste contains organic materials that can be utilized to help improve soil fertility. This study aims to determine the effectiveness of applying oil palm waste in enhancing the growth of oil palm seedlings. The research used a Completely Randomized Factorial Design (3 x 3 x 3), indicating the presence of three factors, each consisting of three levels. Factor 1 was Empty Fruit Bunches (EFB) of oil palm, Factor 2 was the dosage of boiler ash, and Factor 3 was the dosage of nitrogen element from urea fertilizer, resulting in 27 treatment combinations. Each treatment was replicated five times, bringing the total number of plants in this study to 135. Data were analyzed with and F-test; at a 5% significance level, further analysis was using Duncan’s New Multiple Range Test (DNMRT). The results indicated that the application of solid oil palm waste, such as EFB, boiler ash, and nitrogen supplementation, did not significantly affect plant growth. The most effective and optimal dosage for promoting oil palm seedling growth was found in the treatment N2P2Q1 (30 g EFB + 30 g boiler ash + 2 g nitrogen). Based on these findings, increasing the dosage of EFB is recommended to further maximize the growth of oil palm seedlings. The results of this study can be utilized by the palm oil industry to integrate waste such as empty fruit bunches (EFB) and boiler ash into site-specific sustainable fertilization systems, thereby helping to reduce dependence on inorganic fertilizers, improve soil fertility, and support better environmental management.